Causality between stock prices and exchange rates in Turkey: Empirical evidence from the ARDL bounds test and a combined cointegration approach - Turgut Türsoy (International Journal of Financial Studies, 2017)
This paper investigates the interaction between stock prices and real exchange rates by applying monthly data from Turkey for the period between January 2001 and September 2016. This study uses the autoregressive distributed lag (ARDL) model and the Error Correction Model (ECM) in order to investigate the existence of a long-run equilibrium relationship between the variables. The evidence reveals that there is a strong long-run cointegration. The robustness of the ARDL bounds test cointegration was confirmed using the newly-developed combined cointegration, which also provided the same evidence for a strong long-run relationship. The Granger causality test results indicate a long-run bidirectional causality between stock prices and real exchange rates, and also a unidirectional causality from the real exchange rates to the stock prices in the short-run. In order to analyze the validity and reliability of the test results, diagnostic tests were applied in both the short-run and long-run models.
Keywords: F31; F41; G12; G15; 330; real exchange rate; stock prices; ARDL bounds test; combined cointegration